THE NEXUS OF LEVERAGE, PROFITABILITY, AND FIRM SIZE ON TAX PLANNING: IS IT MODERATED BY INSTITUTIONAL OWNERSHIP? - Zab Ass'ad Ibrahim; Hari Sulistyo Wibowo; Muhammad Fachry Fahreza; Hakim, Mohamad Zulman; Triana Zuhrotun Aulia; Imas Kismanah (ZILLZELL MEDIA PRIMA, 2025)
Investigating Institutional Ownership Moderates: The Effect of Leverage, Profitability, and Ownership of Company Size on Tax Planning in Consumer Cyclicals Sector Companies listed on the Indonesia Stock Exchange between 2018 and 2023 is the main objective of this study. The study's population consists of consumer cyclical companies that were listed on the Indonesia Stock Exchange between 2018 and 2023. Over the course of three years, 11 companies out of 153 were chosen for this study using the purposive sample technique. Panel Data Regression Analysis is used in this work. Eviews12 software is used in this investigation. According to the study's findings, (1) leverage has no discernible impact on tax planning. (2) Tax planning is not much impacted by profitability. (3) Tax planning is significantly impacted by the size of the company. (4) The impact of leverage, profitability, and company size on tax planning cannot be moderated by institutional ownership.